Omalizumab added to allergen immunotherapy increased the effect of therapy in patients with severe local allergic rhinitis - Andrzej Bozek; Renata Kozłowska; Maciej Misiołek; Wojciech Ścierski; Radosław Gawlik (Taylor & Francis Group, 2022)
Background Allergen immunotherapy (AIT) is effective in patient with local allergic rhinitis (LAR). However, AIT may not always achieve the optimal treatment effect. Objective To present short study with clinical cases of LAR combined therapy with sublingual immunotherapy (SLIT) and omalizumab in patients with house dust mite (HDM) allergy and compared it to therapy with omalizumab alone. Methods Patients with severe LAR and hypersensitivity to HDMs were included. SLIT for HDMs was launched in a perennial protocol using SQ-HDM SLIT tablets with omalizumab. The total rhinitis symptom score (TRSS), total medication score (TMS) and combined total score (CTS) were assessed after one year. Results After 12 months, significant improvements in all analyzed parameters in the patients on SLIT+ omalizumab therapy were observed: a reduction in the TRSS from 1.21 ± 0.33 to 0.6 ± 0.28 (p < .05), a reduction in the TMS from 2.25 ± 1.05 to 0.88 ± 0.31 (p < .05) and a reduction in the CTS from 3.46 ± 0.57 to 1.48 ± 0.51 (p < .05). This improvement in TRSS, TMS also in CTS was significantly greater than in the rest of the group with SLIT alone or omalizumab alone. Conclusion Omalizumab may be a valuable treatment that increases the effectiveness of immunotherapy in patients with severe LAR.